The role of postoperative radiotherapy for thymomas: a multicentric retrospective evaluation from three Italian centers and review of the literature - Bruni, Alessio (J Thorac Dis, 2020)
BACKGROUND: Thymoma is a rare mediastinal neoplasia. Surgery is the backbone of the treatment, but the role of postoperative radiotherapy (PORT) remains controversial. We aimed to obtain data on survival and safety in patients treated with PORT in three different Italian institutions. METHODS: We retrospectively analyzed 183 consecutive patients who underwent surgery from 1981 to 2015. According to the Masaoka-Koga staging system, 39.3%, 32.7%, 18.6% and 9.8% patients were in stage I, II, III and IV of disease, respectively. PORT was indicated in 114 patients (62.3%), while 69 subjects underwent surgery alone. Complete resection was obtained in 68 patients who underwent PORT. Adverse events (AEs) were graded according to CTCAE v4.0. We analyzed the recent literature to describe the current reports on PORT for resected thymoma. RESULTS: Mean follow-up was 130 months (range, 3–417 months). Overall survival (OS) at 1-, 5- and 10-year from surgery was 98.3%, 90.2% and 69.7% respectively. One-, 5- and 10-year disease specific survival (DSS) was 98.9%, 92.3% and 89.8% respectively. Disease free survival (DFS) at 1, 5 and 10 years from surgery was 96.7%, 88.3% and 82.8% respectively. Univariate analysis showed that complete resection, cell histology A-AB-B1 and stages I–II were significant predictors of better DSS and DFS. Multivariate analysis showed that sex, R0 margins and WHO histology was independent prognostic factors. Among patients treated with PORT, a trend towards better OS was evident with Masaoka stage I–II (P=0.09). Patients with R0 margins treated with PORT showed better OS and DSS (P=0.05). No differences in DSS for performance status (P=0.70), WHO histology (P=0.19), paraneoplastic syndrome (P=0.23) and surgical procedure (P=0.53) were evident. Patients treated with PORT had a higher level of acute AEs compared to surgery alone, but none of these was graded ≥3. CONCLUSIONS: Our results confirmed that patients with incompletely resected thymoma had the worst OS and DSS. High grade acute toxicity was not different between PORT and surgery alone. Other trials reported a significant benefit in OS, DSS and DFS in stage IIb–IV thymoma treated with PORT.